Functional, communicative and critical health literacy among older Polish citizens - Anna Mirczak (Medycyna Pracy, 2022)
Background The level of health literacy possessed by an individual (functional, communicative, critical) determines their ability to effectively self-manage a chronic disease. The aim of the study was to assess the level and functional, communicative, and critical determinants of health literacy in the group of chronically ill older adults.